Automatic 3d building extraction from stereo Ikonos images - Xiong, Z. (2014)
American Society for Photogrammetry and Remote Sensing - Annual Conference of the American Society for Photogrammetry and Remote Sensing 2006: Prospecting for Geospatial Information Integration